Efecto de la variación de la relación polvo / asfalto sobre la durabilidad de mezclas asfálticas - Benavides-Solera, María Alejandra (Instituto Tecnológico de Costa Rica, 2016)
The question that motivated this research was the need to know if the ratio of mineral dust / effective asphalt content is a relevant parameter by itself, not by correlation with other properties, since currently the Ministry of Public Works can reject asphalt mixes only because of unacceptable mineral dust / effective asphalt content ratios, whereas other indicators might show compliance. Different mixtures were manufactured at the laboratory with the mix design optimum asphalt content applied at the actual mixing plant from MOPT at Siquirres. Also mixes with dust / effective asphalt content ratios of 1.0, 1.3 and 1.7 were manufactured and tested by diametral tension, stability and flow, and resilent modulus. Therefore it was possible to gain some knowledge on whether or not it might be feasible to change the current standard. As for the results, it was determined that there isn´t a strong evidence of connection between the performance of the mixture and the dust / effective asphalt content, and there might be some much more important parameters to judge a mixture peformance.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Polvo; Mineral; Asfalto; Durabilidad; Resistencia